2021
DOI: 10.3389/fneur.2021.652177
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fatigue Severity With Maladaptive Coping in Multiple Sclerosis: A Data-Driven Psychodynamic Perspective

Abstract: Fatigue in persons with multiple sclerosis (PwMS) is severely disabling. However, the underlying mechanisms remain incompletely understood. Recent research suggests a link to early childhood adversities and psychological trait variables. In line with these studies, this paper took a psychodynamic perspective on MS-fatigue. It was hypothesized that fatigue could represent a manifestation of maladaptive coping with intense emotions. The schema therapeutic mode model served as a theoretical and empirically valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
3
0
2
Order By: Relevance
“…In cognitive and motor fatigue, the distinction from fatigability is helpful in determining the extent of functional components ( 24 ). Furthermore, dissociative coping styles in pwMS seem to significantly increase fatigue ( 25 ). Including these symptoms can also be considered a strength of this study since it allows us to take into account the reality of everyday clinical practice where such symptoms are often present.…”
Section: Discussionmentioning
confidence: 99%
“…In cognitive and motor fatigue, the distinction from fatigability is helpful in determining the extent of functional components ( 24 ). Furthermore, dissociative coping styles in pwMS seem to significantly increase fatigue ( 25 ). Including these symptoms can also be considered a strength of this study since it allows us to take into account the reality of everyday clinical practice where such symptoms are often present.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first step to disentangling the conundrum of post-COVID syndrome (8). Symptoms may also be related to psychosocial stress, trauma, or maladaptive coping style (43,44). In contrast, common practice identification of an organic cause does not exclude psychological or psychiatric comorbidities and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological factors can also interfere with the origin of fatigue. Pust et al [ 34 ] demonstrated that psychological trauma in childhood can interfere with the perception of CF in patients with multiple sclerosis as a defence mechanism, leading to the assumption that the trauma of the diagnosis or the initial phase of TAK might increase the perception of CF in these patients, possibly by CNS mechanisms found in chronic pain.…”
Section: Discussionmentioning
confidence: 99%